F(g(x))
sub g(x) for every x in f(x)
f(g(x))=2(g(x))-4
f(x^2)=2(x²)-4
f(g(x))=2x²-4
Answer:
B
Step-by-step explanation:
combine like terms
these steps use exponent laws
a few key ones i used:
(x^y^z) = x^(y*z)
x^y * x^z = x^(y+z)
let me know if you have any questions!
Step-by-step explanation:
y = 28
<em><u>plz</u></em><em><u> </u></em><em><u>mark</u></em><em><u> my</u></em><em><u> answer</u></em><em><u> as</u></em><em><u> brainlist</u></em><em><u> plzzzz</u></em><em><u> vote</u></em><em><u> me</u></em><em><u> also</u></em><em><u> </u></em><em><u>.</u></em><em><u>.</u></em><em><u>.</u></em><em><u>.</u></em><em><u>.</u></em>
Answer:
256m^2
Step-by-step explanation:
you can cut up the figure.
A1=bh
A1= 24x8
A1=192m^2
A2=bh
A2= bh
A2=8x8
A2=64m^2
A1+A2= Atotal
A=192+64
A=256m^2